Incorporating singing as a tool for teaching phrasing among piano teachers in Klang Valley Malaysia / Ng Weng Seng - Ng , Weng Seng (2021)
One of the main difficulties that a piano student may encounter is to shape a phrase musically. In general, these phrases may lack direction, shape and expression, thus affecting the student’s interpretation in performance. Most researchers agree that the voice is the most natural instrument and that listening to good singers will help to develop musicality and good phrasing in piano playing. The purpose of this research was to find an effective approach to incorporating singing as an aid to piano playing. This study investigated how piano teachers in the Klang Valley of West Malaysia have incorporated singing as a teaching tool in piano lessons in order to teach phrasing in music. A qualitative research approach was employed. Ten semi-structured interviews were conducted to discover the teachers’ perspectives on the use of singing as one of the tools to improve phrasing in their students’ piano playing. This was followed by 15 observations of the lessons given by five piano teachers to see how the inclusion of singing affected the students’ phrasing of the music. The results indicated that the use of singing as an aid in teaching phrasing had positive effects in terms of having a better understanding of the phrase structure, breath points, shaping, dynamic contrasts, tone colour and direction of the phrases. The results also showed that the physical gesture of breathing in singing helped to promote better phrasing and shaping in musical performance. Furthermore, the results found that listening and appreciating the elements in good singing helped the students to improve their musical interpretation and heighten their understanding of good sound. There were three novel findings, namely, listening to good classical singing would build musicianship and musicality from the early stages of music learning, singing was used to teach voicing and to improve the awareness of fingering in piano playing. This study argues that such an approach will promote better phrasing in musical performance.